Retrotransposon-based genetic diversity of Deschampsia antarctica Desv. from King George Island (Maritime Antarctic) - Androsiuk, Piotr; Chwedorzewska, Katarzyna J.; Dulska, Justyna; Milarska, Sylwia; Giełwanowska, Irena (Zenodo, 2021)
Deschampsia antarctica Desv. can be found in diverse Antarctic habitats which may vary considerably in terms of environmental conditions and soil properties. As a result, the species is characterized by wide ecotypic variation in terms of both morphological and anatomical traits. The species is a unique example of an organism that can successfully colonize inhospitable regions due to its phenomenal ability to adapt to both the local mosaic of microhabitats and to general climatic fluctuations. For this reason, D. antarctica has been widely investigated in studies analyzing morphophysiological and biochemical responses to various abiotic stresses (frost, drought, salinity, increased UV radiation). However, there is little evidence to indicate whether the observed polymorphism is accompanied by the corresponding genetic variation. In the present study, retrotransposon-based iPBS markers were used to trace the genetic variation of D. antarctica collected in nine sites of the Arctowski oasis on King George Island (Western Antarctic). The genotyping of 165 individuals from nine populations with seven iPBS primers revealed 125 amplification products, 15 of which (12%) were polymorphic, with an average of 5.6% polymorphic fragments per population. Only one of the polymorphic fragments, observed in population 6, was represented as a private band. The analyzed specimens were characterized by low genetic diversity (uH e = 0.021, I = 0.030) and high population differentiation ( F ST = 0.4874). An analysis of Fu's F S statistics and mismatch distribution in most populations (excluding population 2, 6 and 9) revealed demographic/spatial expansion, whereas significant traces of reduction in effective population size were found in three populations (1, 3 and 5). The iPBS markers revealed genetic polymorphism of D. antarctica , which could be attributed to the mobilization of random transposable elements, unique features of reproductive biology, and/or geographic location of the examined populations.